Minimizing Radiation Exposure in Evaluation of Pediatric Head Trauma: Use of Rapid MR Imaging - Mehta, H.; Acharya, J.; Mohan, A.L.; Tobias, M.E.; LeCompte, L.; Jeevan, D. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: With >473,000 annual emergency department visits for children with traumatic brain injuries in the United States, the risk of ionizing radiation exposure during CT examinations is a real concern. The purpose of this study was to assess the validity of rapid MR imaging to replace CT in the follow-up imaging of patients with head trauma.MATERIALS AND METHODS: A retrospective review of 103 pediatric patients who underwent initial head CT and subsequent follow-up rapid MR imaging between January 2010 and July 2013 was performed. Patients had minor head injuries (Glasgow Coma Scale, >13) that required imaging. Initial head CT was performed, with follow-up rapid MR imaging completed within 48 hours. A board-certified neuroradiologist, blinded to patient information and scan parameters, then independently interpreted the randomized cases.RESULTS: There was almost perfect agreement in the ability to detect extra-axial hemorrhage on rapid MR imaging and CT (κ = 0.84, P < .001). Evaluation of hemorrhagic contusion/intraparenchymal hemorrhage demonstrated a moderate level of agreement between MR imaging and CT (κ = 0.61, P < .001). The ability of MR imaging to detect a skull fracture also showed a substantial level of agreement with CT (κ = 0.71, P < .001). Detection of diffuse axonal injury demonstrated a slight level of agreement between MR imaging and CT (κ = 0.154, P = .04). However, the overall predictive agreement for the detection of an axonal injury was 91%.CONCLUSIONS: Rapid MR imaging is a valid technique for detecting traumatic cranial injuries and an adequate examination for follow-up imaging in lieu of repeat CT.rMRIrapid MR imaging